Refractory Coeliac Disease: Diagnosis, Treatment, and Emerging Therapies - Starzyk, Agnieszka; Charzewski, Piotr (Quality in Sport, 2025)
Coeliac disease (CD) is a chronic immune-mediated disorder triggered by gluten ingestion in genetically predisposed individuals, leading to intestinal damage, malabsorption, and systemic complications. Although traditionally considered a gastrointestinal disorder, CD is now recognized as a multisystem condition with neurological, musculoskeletal, endocrine, and cardiovascular manifestations. Despite advancements in diagnostic tools, the disease remains underdiagnosed due to its diverse clinical presentations. The global prevalence of CD is approximately 1%, with increasing incidence linked to improved screening and environmental factors. Diagnosis involves serological testing, histological examination, and, in select cases, genetic screening. While strict adherence to a gluten-free diet (GFD) is currently the only effective treatment, many patients face dietary compliance challenges, nutritional deficiencies, and persistent symptoms, necessitating further investigation for refractory CD. Findings highlight that while GFD remains the cornerstone of treatment, adherence difficulties and ongoing symptoms in some patients require alternative interventions. Research into immune modulation, gut microbiota therapies, and intestinal permeability regulation is ongoing, with promising developments for non-dietary treatment options.